Implementation of a web-based laundry application with the laravel framework for laundry Aisy Laundry - Muhammad Faisal; Priyono; Riswandi Ishak; Elin Panca Saputra; Tino Dwiantoro; Sugiono; Dyah Ayu Astuti; Muhammad Amir Hasan (Institute of Computer Science (IOCS), 2023)
Aisy Laundry is a laundry service business located in Tambun, South Bekasi. The administrative service process at the site is still manual, paper and books are still used for recording transaction data and preparing reports. the purpose of this research is to complement the needs of users or users who can make it easier to do input so as to optimize the time used. in that place they still use paper and books, they still record transaction data in making reports. Paper media is susceptible to damage, tearing, loss and humidity, making it difficult to find the required data, a time-consuming process, and errors often occur during recording. Therefore, a laundry service application program was created. The development of this program uses the waterfall method, namely creating a database using a programming language and designing software using the web-based Laravel Framework by creating several features such as logins, User Data, Customer Data, Laundry Service Data, Account Data, Payment Transaction Data and Transaction Report Data. With this program, it can be a solution to help facilitate transaction creation and reporting, as well as increase the effectiveness and efficiency of an optimal work system at Aisy Laundry.